Advertising agency compensation, client evaluation and switching costs: an extension of agency theory - Davies, Mark; Prince, Melvin (Journal of Current Issues and Research in Advertising, 2010)
We develop a theory of advertising agency compensation, client evaluation and switching costs, with extensions to agency theory. When clients are exposed to high switching costs, they become more vulnerable to the risk of agency costs. In response, clients can select compensation and evaluation decisions that convey fairness, signal their commitment, and invite agency reciprocity. With high switching costs, outcome-based compensation and formal evaluation procedures are likely. High switching costs are associated with signifi'cant relationship investments, mature relationships, large clients, formal evaluation, and with clients that use their agencies as strategic partners. Clients surveyed in North America support the theory. © 2010 Taylor and Francis Group, LLC.
16 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/011-534-427-868-948 tex.type: [object Object]
Keywords: dept.mkt